SPARC in cancer‐associated fibroblasts is an independent poor prognostic factor in non‐metastatic triple‐negative breast cancer and exhibits pro‐tumor activity. Issue 6 (30th November 2022) - Alcaraz, Lindsay B.; Mallavialle, Aude; Mollevi, Caroline; Boissière‐Michot, Florence; Mansouri, Hanane; Simony‐Lafontaine, Joelle; Laurent‐Matha, Valérie; Chardès, Thierry; Jacot, William; Turtoi, Andrei; Roger, Pascal; Guiu, Séverine; et al.
Abstract: Triple‐negative breast cancer (TNBC) is the most aggressive breast cancer subtype and lacks specific targeted therapeutic agents. The current mechanistic evidence from cell‐based studies suggests that the matricellular protein SPARC has a tumor‐promoting role in TNBC; however, data on the clinical relevance of SPARC expression/secretion by tumor and stromal cells in TNBC are limited. Here, we analyzed by immunohistochemistry the prognostic value of tumor and stromal cell SPARC expression in 148 patients with non‐metastatic TNBC and long follow‐up (median: 5.4 years). We also quantified PD‐L1 and PD‐1 expression. We detected SPARC expression in tumor cells (42.4%), cancer‐associated fibroblasts (CAFs; 88.1%), tumor‐associated macrophages (77.1%), endothelial cells (75.2%) and tumor‐infiltrating lymphocytes (9.8%). Recurrence‐free survival was significantly lower in patients with SPARC‐expressing CAFs. Multivariate analysis showed that SPARC expression in CAFs was an independent prognostic factor. We also detected tumor and stromal cell SPARC expression in TNBC cytosols, and in patient‐derived xenografts and cell lines. Furthermore, we analyzed publicly available single‐cell mRNA sequencing data and found that in TNBC, SPARC is expressed by different CAF subpopulations, including myofibroblasts and inflammatory fibroblasts that are involved in tumor‐related processes. We then showed that fibroblast‐secreted SPARC had a tumor‐promoting role by inhibiting TNBC cell adhesion and stimulating their motility and invasiveness. Overall, our study demonstrates that SPARC expression in CAFs is an independent prognostic marker of poor outcome in TNBC. Patients with SPARC‐expressing CAFs could be eligible for anti‐SPARC targeted therapy. Abstract : What's new? In vitro evidence suggests that the matricellular protein SPARC has a tumor‐promoting role in triple‐negative breast cancer (TNBC). However, the clinical relevance of SPARC in triple‐negative breast cancer remains unclear. Here, the authors analyzed the prognostic value of tumor and stromal SPARC in 148 patients with non‐metastatic TNBC. SPARC was most often expressed by myofibroblasts and inflammatory cancer‐associated fibroblasts (CAFs), and fibroblast‐secreted SPARC exhibited a tumor‐promoting role in TNBC. Moreover, SPARC expression in CAFs was an independent prognostic marker of poor outcome. This study points to CAF‐derived SPARC as a potential novel therapeutic target in triple‐negative breast cancer.